A Game-Theoretic Analysis of Multiple Protocol Data Flows in Hierarchical M2M Communication Networks. (20th November 2013) - Wang, Gang; Leng, Jie; Bai, Lin
Abstract : A hierarchical machine-to-machine (M2M) communication network, where multiple heterogeneous devices compete for transmission on congested links, is considered. In such a network, the cluster headers gather the network coding and routing messages from multiple M2M devices and forward them to the cellular network. We propose a novel discriminatory user-based utility mechanism for network coding users and routing users. The price of anarchy (PoA), which is used to characterize the worst-case efficiency bounds, is analyzed. The simulation results show that network coding could promote the efficiency to a certain extent.